Integrated analysis from multicentre studies identities m7G-related lncRNA-derived molecular subtypes and risk stratification systems for gastric cancer - Ma, Mingwei; Li, Jie; Zeng, Ziyang; Zheng, Zicheng; Kang, Weiming (Frontiers in Immunology, 2023)
Gastric cancer (GC) is the third leading cause of cancer death worldwide. Due to the lack of effective chemotherapy methods for advanced gastric cancer and poor prognosis, the emergence of immunotherapy has brought new hope to gastric cancer. Further research is needed to improve the response rate to immunotherapy and identify the populations with potential benefits of immunotherapy. It is unclear whether m7G-related lncRNAs influence tumour immunity and the prognosis of immunotherapy. This study evaluated 29 types of immune cells and immune functions in gastric cancer patients, and m7G-related lncRNAs and their molecular subtypes were identified. The results showed that among the three molecular subtypes, the B subtype had the highest level of infiltration, and the B subtype may benefit more from immunotherapy. In addition, we also studied the biological function characteristics of m7G-related lncRNA molecular subtypes and divided GC patients into two regulator subtypes. The two subtypes have significant immunological differences and can be used to judge ICI treatment. Finally, the patient's risk score was calculated based on m7G-related lncRNAs, resulting in a risk score formula based on five lncRNAs, including LINC00924, LINC00944, LINC00865, LINC00702, and ZFAS1. Patients with poor prognoses were closely related to patients in the high-risk group, and a nomogram of staging and risk groups was established to predict the prognosis. After comprehensive analysis of different risk groups, the efficacy of the high-risk group on bleomycin, cisplatin, docetaxel, doxorubicin and etoposide was better than that of the low-risk group, suggesting that risk subgroups based on risk scores play a guiding role in chemotherapy and that the high-risk group may benefit more from immunotherapy. For experimental verification, RT–qPCR results from the native cohort showed that LINC00924, LINC00944, and LINC00865 were highly expressed in tumour tissues, while LINC00702 and ZFAS1 were expressed at low levels in tumour tissues. In conclusion, we were the first to discover that m7G-related lncRNAs play a vital role in the tumour immune microenvironment of gastric cancer, and a risk prediction model was established to identify patients with potential benefits of immunotherapy and predict the prognosis of GC patients.